The history of the short novel internationally and in the Arab world: (roots, origins, development) - Ezzat, Ass.Lecture. Ammar Ibrahim; Ghazi, Prof. Dr. Fawzia Laayous (Thi Qar Arts Journal, 2023)
The novella was known to the Arabs at a relatively late stage from Europe, for many reasons, the most important of which is the problematic and instability of the term. In Egypt, the term short novel did not take its place on the map of literature until the beginning of the second half of the twentieth century. In the sixties, the novella became a fictional form, which most experienced. The novelists of that period, and even some writers, most of their productions belonged to the novella form (1), but it did not take its right to study until the second half of the eighty decade (2), to settle as a stand-alone literary genre. In Iraq, there is no accurate database on (the novella): its roots, origin, and development, just as the references broadcast in critical books do not help us in drawing or forming a clear picture of this literary genre. Creativity by male and female writers, and with the positive reception of a wide range of readers for these types of stories, contemporary critical studies emerged that framed these literary genres and studied them within a broader field, which is (fictional art) before joining the narrative as a science that accommodates all narrative forms, literary and non-literary, oral. and written. The short novel (novel) remained a literary genre between the long novel and the short story. It was studied by researchers, once, as a novel. And at other times, as a short story or a long story, and it did not acquire its identity until late at the end of the last century.